PROCESSING OF ASBUTON BITUMEN USING FLOTATION METHOD - Aldiyansyah
Buton Island, which is located in Southeast Sulawesi, has natural asphalt reserves, namely buton asphalt which is spread from sampolawa to lawele. Buton asphalt deposits amounted to 650 million tons with varying bitumen content which is estimated to be equivalent to 170 million tons of oil asphalt. The advantages of buton asphalt include higher pavement stability compared to oil asphalt and are more resistant to weather and can save pavement thickness by 22%. Asbuton can be used as an alternative material to replace oil asphalt after bitumen can be separated from the impurity minerals. Bitumen is a good adhesive and waterproofing agent and has good resistance to oxidation reactions. This study is conducted to separate Asbuton bitumen from impurity minerals using the flotation method. Flotation experiments were carried out on 1375 mL volume flotation cells. Kerosine and oleic acid are used as collectors and pine oil as frother. The purpose of this study is to increase the level of bitumen and also the recovery. Flotation was carried out at a fraction size of -200 mesh. Variations made in this experiment were variations in pH (5,6,7,8), collector doses (150,200,250, and 300 gr / ton), and solid percent (20,25,30,35%). Asbuton bitumen characterization was carried out using a microscope, SEM-EDS, XRD, XRF, and FTIR. The resulting concentrate and tailings were then analyzed using the Sokhlet method to determine Asbuton bitumen levels. The experimental results showed an increase in bitumen levels. The variation of pH carried out showed an increase in the optimum yield of bitumen at pH 7 using kerosene collectors, namely concentrations of 38.7% with an recovery of 85.81%. In the variation of the collector doses showed an increase in bitumen levels shown at a doses of 150 gr /ton which is 34.4% with recovery of 52.54%. In the percent variation, solid shows an increase in bitumen levels, namely 20% solid percent with a level of 35.4% with recovery of 72.95%.